2022
DOI: 10.1155/2022/6063418
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Research on the Driving Factors of Constructing Innovative Thinking Environment from the Perspective of Online Community

Abstract: With the development of Internet information technology, the Internet space and the real space are increasingly integrated, and the influence of the Internet community has surpassed the cyberspace. The online community is not only a product of virtual space, but also integrates with the real society in terms of community interaction mode, network communityization of geographic communities, and dematerialization of social organizations. This offline integration trend objectively requires changes in online commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The development of the Internet makes this willingness easy to achieve. In the context of information globalization, people's perception of space are shaped by network and social media [27], It breaks through the limitations of time and space, and the internesting of virtual space and real space enables the single mobile individual in the real community and network community who pursue similar food purchasing ways or food quality [28,29]…”
Section: Every Morning He Posts What He Sells Today and At What Price...mentioning
confidence: 99%
“…The development of the Internet makes this willingness easy to achieve. In the context of information globalization, people's perception of space are shaped by network and social media [27], It breaks through the limitations of time and space, and the internesting of virtual space and real space enables the single mobile individual in the real community and network community who pursue similar food purchasing ways or food quality [28,29]…”
Section: Every Morning He Posts What He Sells Today and At What Price...mentioning
confidence: 99%
“…Divergent thinking encapsulates attributes such as fluency and flexibility. Fluency predominantly manifests in swift and adaptable thinking, adeptness in imagination, and the capacity to articulate numerous pivotal points and principles within a constrained timeframe (Xin & Shi, 2022). It facilitates both vertical and horizontal connections, culminating in a holistic comprehension.…”
Section: Concrete Embodiment Of Cultivating Students' Mathematical Co...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%